PERSEPSI WISATAWAN TERHADAP WISATA PANTAI TIRAM DI NAGARI TAPAKIH KECAMATAN ULAKAN TAPAKIH KABUPATEN PADANG PARIAMAN, SUMATERA BARAT INDONESIA - Septian, Shandy; Hasnah, Hasnah; Fitriana, Widya (AGROTEKSOS; Vol 35 No 2 (2025): Jurnal Agroteksos Agustus 2025, 2025)
The perception of tourists can reflect the level of satisfaction with facilities, cleanliness, accessibility, and services for sustainability and a more effective promotion strategy to increase the number of tourist visits, especially at Tiram Beach. The purpose of this study is to (a) describe the condition of tourism at Tiram Beach and (b) analyze tourists' perceptions of tourism at Tiram Beach Nagari Tapakih, Ulakan Tapakih District, Padang Pariaman Regency, West Sumatra Indonesia. This research uses qualitative and quantitative approaches with survey methods with the 4A concept (attraction, amenity, accessibility, ancillary) to find specifically and realistically people's perceptions of Tiram Beach. The condition of Tiram Beach tourism shows that this beach has natural scenery and a calm atmosphere, away from noise. There are infrastructure facilities such as parking facilities, places of worship, restaurants, and location plans. In addition, Tiram Beach is easily accessible because it is not too far from Padang City or Pariaman City. The perception of tourists towards Tiram Beach is in the positive category as seen from the 4A of attraction with a score of 3,644, accessibility with a score of 4,840, amenity with a score of 10,640, and ancillary with a score of 3,576. Recommendations that can be given to improve the quality of Tiram Beach Tourism can be done by optimizing tourist facilities and improving the quality of 4A Services that are more attractive, comfortable, and sustainable for tourists and provide economic benefits for the local community.